Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

Les pratiques musicales autochtones : une confluence de perspectives - Beaudry, Nicole (Traité de la culture, 2002)

The Sound System: Contributions to Jamaican Music and the Montreal Dancehall Scene - Constantinides, John (Université de Montréal, 2002)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.
Publisher: [Florian Noetzel GmbH Verlag, VWB - Verlag für Wissenschaft und Bildung, Schott Music GmbH & Co. KG, Bärenreiter]

Considering Complexity in Canadian Civil Society: A Case Study of Studio XX - Gerlach, Neil; Hamilton, Sheryl (Revista Mexicana de Estudios Canadienses, 2002)

Virtually Civil: Studio XX, Feminist Voices, and Digital Technology in Canadian Civil Society - Gerlach, Neil; Hamilton, Sheryl N. (Civic Discourse and Cultural Politics in Canada, 2002)

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

L'homme qui fait chanter les femmes : Stéphane Venne - Joubert, Lucie (Lectures du genre, 2002)

Ma vie, je t'aime - Martel, Renée; Chapados, Dominique (Éditions Publistar, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)
Publisher: SAGE Publications Ltd

Les cahiers noirs de Lynda Lemay - Paquette, Claude (Éditions Contreforts, 2002)

Chansons d'amour et roman sentimental populaire : quand l'air ne fait pas la chanson - Savoie, Chantal (Littérature populaire et culture médiatique, 2002)